Sobreviví Como Flor De La Sierra: Women, Violence, and Resistance in Peru - Espinoza, Damarys (My University, 2014)
Drawing upon twelve months of ethnographic fieldwork conducted between 2009 and 2012, this dissertation explores the experiences and lives of primarily indigenous, rural-to-urban migrant women living in grassroots domestic violence shelters in and around Lima, Peru. It examines the institutional barriers women face, as well as the difficult choices and creative solutions they practice as they attempt to leave abusive relationships. It investigates the responses of social institutions and the state to intimate partner violence, and the impact that limited resources pose on the quality and consistency of intervention services made available to women in grassroots shelters. To shed light on these phenomena, I ground this participatory ethnography in the stories and lived experiences of women living in shelters as well as shelter directors and advocates, and advance three central arguments. First, I argue that women's experiences of intimate partner violence are connected to broader forms of violence, including institutional and structural violence. Second, I argue that displacement and migration, racialization, and class inequality are critical factors shaping the experience of intimate partner violence among women. Third, I argue that while grassroots shelters fill a crucial need for women who are denied resources from social institutions and the state, and provide a space where women exercise agency by practicing transformational survival strategies, limited resources impact intervention services that shelters can provide to women who experience violence from an intimate partner. By focusing on women's attempts to navigate structures that produce and reproduce violence, and the role that grassroots shelters perform in helping women rebuild their lives, I hope that this dissertation draws attention to manifestations of individual and collective resistance that have the potential to transform approaches to intimate partner violence. In also exposing how agency and resistance are constrained, however, I hope that this dissertation makes clear the persistent flaws and contradictions inherent in policy and legal frameworks currently in place in Peru.
Thesis (Ph.D.)--University of Washington, 2014
Keywords: Critical Ethnography; Gender-Based Violence; Peru; Women; Cultural anthropology; Gender studies; Latin American studies; anthropology